The role of technology in mortgage lending - Andreas Fuster; Matthew Plosser; Philipp Schnabl; James Vickery (Federal Reserve Bank of New York, 2018)
Technology-based ("FinTech") lenders increased their market share of U.S. mortgage lending from 2 percent to 8 percent from 2010 to 2016. Using market-wide, loan-level data on U.S. mortgage applications and originations, we show that FinTech lenders process mortgage applications about 20 percent faster than other lenders, even when controlling for detailed loan, borrower, and geographic observables. Faster processing does not come at the cost of higher defaults. FinTech lenders adjust supply more elastically than other lenders in response to exogenous mortgage demand shocks, thereby alleviating capacity constraints associated with traditional mortgage lending. In areas with more FinTech lending, borrowers refinance more, especially when it is in their interest to do so. We find no evidence that FinTech lenders target marginal borrowers. Our results suggest that technological innovation has improved the efficiency of financial intermediation in the U.S. mortgage market.
Keywords: D14; D24; G21; G23; 330; mortgage; technology; prepayments; nonbanks